Metastatic follicular carcinoma of the thyroid presenting with thyrotoxic induced impaired control of diabetes mellitus. Issue 725 (March 1986) - Samanta, A.; Burden, A. C.; Jones, G. R.; Nicol, N. T.
Abstract : We report a patient with pulmonary and bony metastases due to follicular carcinoma of the thyroid, occurring 12 years after the initial diagnosis. This was brought to light by worsening diabetic control due to thyrotoxicosis from functioning malignant thyroid tissue. Following radio-active iodine therapy, she remains well with good control of her diabetes.